Improving Basic Design courses through Competences of Tuning MEDA - Rafee Hakky (Universidad de Deusto, 2016)
It is well established that Tuning's development of the concept of competences for the improvement of what is referred to as student-centered approach has proven itself beneficial in developing higher education programs.[1] This paper examines the application of competences suggested by Tuning-MEDA to the benefit of teaching architecture. Two courses were selected from the Architectural Engineering Program at the International University for Science and Technology, Damascus, Syria; namely, Basic Design I and II. Five competences were selected as crucial to be achieved in these two courses: ability to think, perceive and conceive spaces three dimensionally and communicate verbally, in writing, graphically, and/or volumetrically; have critical thinking, analysis and synthesis; knowledge of aesthetics and arts, and understanding their role as key factors in the quality of architectural thinking and design; possess a high level of interpersonal skills; and appreciation of the social and cultural role of architecture. The two courses are evaluated at two levels before being examined in relation to their ability to achieve these competences. They were looked at in connection with Bloom's Taxonomy and found to be able to deliver learning at its upper levels; namely, analysis, synthesis, and evaluation. They were also examined against the typical Learning Retention Pyramid and were found to provide learning opportunities through learning techniques which provide a high level of retention: demonstration, group discussion, and practice by doing. Finally, it was found that the five competences assigned to the courses were very much achievable and indeed through applying them, the two courses were more focused and could achieve their objectives more successfully. [1] Robert Wagenaar, "Competences and learning Outcomes: a Panacea for Understanding the (New) Role of Higher Education?" Tuning Journal for Higher Education 1, no. 2 (May 2014): 279-302.